Pencarian Pelayanan Persalinan Ibu Hamil Risiko Tinggi di Puskesmas Waruroyom Kabupaten Cirebon - Amdad Amdad; Detty Siti Nurdiati; Atik Tri Ratnawati (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Efforts of high-risk pregnant women to search service for childbirth in public health center ofWaruroyom Purpose The study explored the behavior of women with a high-risk pregnancy to search service for childbirth in public health center of Waruroyom Cirebon.MethodA case study involved pregnant and maternal mothers with a high-risk pregnancy, parents, husbands, and midwives. The informants were chosen by purposive sampling, data collection through observation, in-depth interview and focus group discussion. ResultsWomen with high-risk pregnancy searched service for childbirth from midwives, public health center, and hospital. Pregnant women prefer midwives due to familiarity, close location, past experience, attitudes and quality of services. Women with high-risk pregnancy went to the public health center or hospital, did not because of the intentions of themselves but midwives' advice. ConclusionPregnant women did not know if they have a high-risk pregnancy. Midwives provide information about high-risk pregnancy at the end of pregnancy.